Progress in animal nutrition - Richardson, D. (Kansas Agricultural Experiment Station, 2011)
Not one nutrient has been created, yet tremendous progress has been made in the relatively new field of animal nutrition, primarily by scientific investigations that have more clearly defined nutrient needs and interrelationships in the animal body and more knowledge of nutrient content and availability in various feedstuffs. Contributions also have been made by improved feedstuff preparation, animal breeding, management, and disease control.
Keywords: Protein; Fat; Minerals; Animal nutrition